DIGITAL TRANSFORMATION IN THE TAXATION SYSTEM: GLOBAL OPPORTUNITIES AND CHALLENGES - Andi Andi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Digital transformation in the taxation system is a strategic step that can improve efficiency and transparency in global tax collection. With the use of digital technologies such as automation, data analytics, and blockchain, the taxation system can become more accurate, reduce the risk of fraud, and improve public trust. The tax payment process can also be simplified, increasing taxpayer compliance. However, this transformation also presents challenges such as the need for large investments in technological infrastructure, human resource training, and cybersecurity threats that must be managed effectively. In addition, regulatory adjustments and international coordination are needed to address the complexity of taxation in the digital era. With the right strategy, the opportunities from digital transformation in the taxation system can be optimised, although various challenges need to be carefully addressed.